(untitled) (Physical Education, Health and Social Sciences, 2026)
This study examined the effects of the U.S.–Iran conflict on students’ mental well-being and school attendance in Gilgit-Baltistan. A quantitative, descriptive cross-sectional survey design was used. The population comprised secondary and higher secondary school students, and a sample of 350 students was selected through multistage sampling. Data was collected through a self-developed questionnaire consisting of 40 items excluding demographic information. The instrument measured mental well-being, school attendance, challenges faced by students, and coping and support mechanisms. Data were analyzed using descriptive and inferential statistics, including frequency, percentage, mean, standard deviation, independent sample t-test, one-way ANOVA, correlation, and regression analysis. The findings indicated that the conflict negatively affected students’ mental well-being and school attendance. Female and public-school students reported comparatively higher levels of distress and challenges. The study concluded that crisis-related uncertainty influenced students’ emotional health and educational participation, and it recommended school-based psychosocial support and crisis-sensitive educational strategies.